Penerapan Model Pembelajaran Kooperatif Tipe Group Investigation untuk Meningkatkan Kemampuan Siswa dalam Menyusun Teks - Sukiasih, Made (Journal of Education Action Research, 2018)
The implementation of this classroom action research aimed at finding out whether the Cooperative learning Group Investigation Type can improve students' ability in composing text. The subject of this study was the third grade students of SMP Negeri 2 Singaraja in the odd semester of 2017/2018 Academic Year. The data of this research were collected using learning achievement test while the analysis used was descriptive analysis. After all data were analyzed, it was found an improvement in learning outcomes. The average score of the students before the research was 74.80 with learning completeness 60.53.%. Then, in the first cycle, the average score was 76.69 with learning completeness 73.68%. The results of the second cycle also improved with the average score 77.61 and classical learning completeness 89.47%. It turned out that the results in cycle II had exceeded the criteria proposed according to the indicators of success of the study. Based on the data gained, the researcher concluded that the Cooperative Learning model Group Investigation Type can improve the ability of students composing the text.